1997
DOI: 10.1097/00008483-199707000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure as an Adjunct to a Pulmonary Rehabilitation Program

Abstract: Acupressure seems to be useful to patients with COPD as an adjunct to a PRP in reducing dyspnea. Some persons who are not initially familiar with traditional Chinese medicine can learn and will accept self-administered acupressure as part of their self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 7 publications
2
38
0
Order By: Relevance
“…The symptom scores for bronchiectasis and dyspnea in COPD were significantly improved in the acupressure groups in comparison with the control groups. 26,27 The results of the present review were similar to those of Robinson et al, who conducted a systematic review of Shiatsu or acupressure, including self-acupressure and acupressure performed by practitioners. 16 This review included three studies of COPD and two studies of bronchiectasis.…”
Section: Respiratory Diseasesupporting
confidence: 86%
See 1 more Smart Citation
“…The symptom scores for bronchiectasis and dyspnea in COPD were significantly improved in the acupressure groups in comparison with the control groups. 26,27 The results of the present review were similar to those of Robinson et al, who conducted a systematic review of Shiatsu or acupressure, including self-acupressure and acupressure performed by practitioners. 16 This review included three studies of COPD and two studies of bronchiectasis.…”
Section: Respiratory Diseasesupporting
confidence: 86%
“…27 One group performed acupressure at seven bilateral acupoints (Zhongfu LU 1, Yunmen LU 2, Dazhui GV 14, Yuji LU 10, Laogong PC 8, Zusanli ST 36, and Hegu LI 4) for 6 weeks, followed by sham acupressure for an additional 6 weeks. The other group performed sham acupressure for the first 6 weeks and real acupressure for the following 6 weeks.…”
Section: Self-acupressure For Respiratory Diseasementioning
confidence: 99%
“…Two studies using acupuncture [50,51], two trials testing acupressure [52,53] and one study evaluating a single treatment with TENS over acupoints (Acu-TENS) [54], all conducted on COPD patients, showed relief of breathlessness in the intervention group. One study testing acupuncture in cancer patients [55] and one in a mixed group with advanced lung disease [56] showed no improvement in breathlessness.…”
Section: Acupuncture and Acupressurementioning
confidence: 99%
“…Acupressure may offer a nice self-administered alternative to invasive acupuncture that requires a trained therapist for each administration. Maa et al [29] have shown that acupressure may be effective at lessening dyspnea and, upon comparing the two techniques, found little difference between the two in decreasing dyspnea [30].…”
Section: Physiologic Factorsmentioning
confidence: 99%